2014
DOI: 10.4103/0019-557x.128166
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic obstructive pulmonary disease and its association with tobacco smoking and environmental tobacco smoke exposure among rural population

Abstract: A field survey was conducted for chronic obstructive pulmonary disease (COPD) epidemiology in the rural field practice area of Kempegowda Institute of Medical Sciences, Bangalore, India, which covers a population of 44,387 to find out the prevalence of COPD in adult subjects of 35 years and above using cluster sampling technique and to determine the association of tobacco smoking, environmental tobacco smoking (ETS) exposure and type of cooking fuel used with COPD. The overall prevalence of COPD was 4.36%. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 2 publications
1
13
1
Order By: Relevance
“…(10,11,12) COPD prevalence was also high in our study because of smoking habit among elderly in our area, even though pollution is not that significant, but it varies in different part of India, it varies in range 3% to 8% in general population. (13,14) In our study it is also found that depression is equally present in both sexes. Prevalence of depressive symptoms varied from 13.5% to 36.8% in community dwelling older adults.…”
Section: Totalsupporting
confidence: 78%
“…(10,11,12) COPD prevalence was also high in our study because of smoking habit among elderly in our area, even though pollution is not that significant, but it varies in different part of India, it varies in range 3% to 8% in general population. (13,14) In our study it is also found that depression is equally present in both sexes. Prevalence of depressive symptoms varied from 13.5% to 36.8% in community dwelling older adults.…”
Section: Totalsupporting
confidence: 78%
“…Studies from other centers in India also paint a similar picture regarding gender and etiology. [111213] A definite delineation could not be made between cigarette and bidi in this study. Females though limited in number were united by a single cause, exposure to biomass fuel in the form of firewood; this mirrored studies across India and in other developing economies.…”
Section: Discussionmentioning
confidence: 85%
“…Similar results were reported in previous studies. [ 20 22 27 ] About 75% of our sample in the study were above the age of 50 years. An Indian Study on Epidemiology of Asthma, Respiratory Symptoms and Chronic Bronchitis in Adults (INSEARECH) involving a total of 85,105 men and 84,470 women from 12 urban and 11 rural showed that the overall prevalence of chronic bronchitis in adults >35 years was 3.49%.…”
Section: Discussionmentioning
confidence: 99%
“…An Indian Study on Epidemiology of Asthma, Respiratory Symptoms and Chronic Bronchitis in Adults (INSEARECH) involving a total of 85,105 men and 84,470 women from 12 urban and 11 rural showed that the overall prevalence of chronic bronchitis in adults >35 years was 3.49%. [ 27 ] Hence, with advancing years COPD is an important comorbidity. There was higher proportion of “non-service holders” (58%) among the sample, and almost 53% were BPL card holders and around 32% of the respondents had a positive family history of COPD.…”
Section: Discussionmentioning
confidence: 99%